Use of Foley's catheter as a tourniquet for the management of vascular lesion of lip in Mowat-Wilson syndrome - Rajeev Pandey; Sanjeev Kumar; Jitender Kumar; Varun Arya; Rishabh Thakker; Minerva Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Vascular malformation of lower lip is a very rare anomaly. The lesion leads to facial asymmetry, difficulty in speech and eating and drooling of saliva. Treatment goals include symmetrical reconstruction of the lip with minimal scarring, provide adequate bulk for the reconstruction of vermillion, in toto removal of the lesion and prevent recurrence. The most common complication during surgical removal of these lesions includes blood loss and profuse bleeding which leads to poor visibility, increased operation time and postoperative requirement of blood transfusion. Therefore, the use of sclerosing agent is recommended before surgical removal. This may help in decreasing bleeding during surgery but not in all cases. Case Report: Here, we report the use of Foley's catheter for the management of a high flow lesion of lower lip in a 12-year-old patient diagnosed with Mowat-Wilson syndrome. This technique helped in providing bloodless field which lead to minimal blood loss and good visibility intraoperatively.